Aptitud anaerobia en deportistas de combate del sexo femenino - Almenares Pujadas, M. E.; Collazo Garay, B. C.; Rodriguez Leal, E. A. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2005)
The aim of this study was investigate the anaerobic fitness in a sample of three female combat sports selections of high qualification: 15 judoists, 7 fencing sable modality and taekwondoists 16. Neuromuscular variables were measured, at the beginning and end of special preparation, using Bosco ergojump and jump ability tests. Descriptive statistics and significance of differences between sports mensurations were determined. Obtained results were: Pala (15,7 ± 2,1-19,2 ± 1,5 W/Kg), Pana (14,5 ± 1,9-17,7 ± 1,2 W/Kg). The highest averages of SCAB, SSAB, SCPD, SCPCD and SDPC were those of fencers and the best coordination was also of fence competitors, while the highest values of CELAS were those of judoists. This study concludes that the obtained results belong together with characteristics of the sport expression that prevail in studied sports.